2022
DOI: 10.1002/prep.202100328
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Melt Curve and Liquid Shear Viscosity of RDX up to 30 GPa

Abstract: Recent grain‐scale simulations of HMX and TATB have shown that predictions for hot spot formation in high explosives are particularly sensitive to accurate determinations of the pressure‐dependent melt curve and the shear viscosity of the liquid phase. These physics terms are poorly constrained beyond ambient pressure for the explosive RDX. We adopt an all‐atom modeling approach using molecular dynamics (MD) simulations to predict the melt curve of RDX near to detonation conditions (30 GPa) and determine the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…We obtained corresponding estimates of T m at atmospheric pressure for the three nonreactive FFs using the phase-coexistence approach. These simulations followed the same general simulation protocol as was applied to obtain the pressure-dependent melting curves for TATB, HMX, and RDX . Our simulations considered melting from the (100) crystal face and used a simulation cell that initially contained a 50 × 5 × 5 crystal supercell (2500 molecules) in contact with a liquid region comprising 2500 molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained corresponding estimates of T m at atmospheric pressure for the three nonreactive FFs using the phase-coexistence approach. These simulations followed the same general simulation protocol as was applied to obtain the pressure-dependent melting curves for TATB, HMX, and RDX . Our simulations considered melting from the (100) crystal face and used a simulation cell that initially contained a 50 × 5 × 5 crystal supercell (2500 molecules) in contact with a liquid region comprising 2500 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…These simulations followed the same general simulation protocol as was applied to obtain the pressure-dependent melting curves for TATB, 52 HMX, 88 and RDX. 89 Our simulations considered melting from the (100) crystal face and used a simulation cell that initially contained a 50 × 5 × 5 crystal supercell (2500 molecules) in contact with a liquid region comprising 2500 molecules. The (100) facet was chosen based on predictions from the Bedrov FF made by Mathew et al, 51 who found that this facet exhibits the fastest melting kinetics and is the least susceptible to overheating among the three "primary" facets (100), (010), and (001).…”
Section: 3mentioning
confidence: 99%
“…14 Indeed, even the oft-followed Arrhenius temperature dependence of liquid shear viscosity cannot be derived from first principles nor the prefactor or activation energy term related to fundamental molecular processes. This shortcoming in theory leaves molecular dynamics (MD) simulations 15,16 and experiments 17–19 as the main methods by which one can obtain data to fit empirical viscosity models.…”
Section: Introductionmentioning
confidence: 99%